Implementasi Etika Bisnis Islam dalam Praktik UMKM Digital: Studi Kasus Transparansi dan Kejujuran di Platform E-Commerce UMKM Fashion - Rosandy, Adrian Bayu (TSARWAH, 2024)
The ongoing development of the technology industry, known as industry 4.0, all types of activities must now be included in digital, including economic activities where MSMEs have started selling products on E-Commerce. Based on data collected by the Ministry of Communication and Information (Kemenkominfo) from 2017 to 2024 there were 405,000 reports of online transaction fraud. As many as 13.1% or 53,055 accidents occurred in e-commerce directly related to online trading. Business ethics include the concepts of honesty, fairness, accountability, and respect for the rights of Muslim consumers, therefore Islamic business ethics are needed to ensure that companies are run in accordance with Islamic law. The results of this study, namely cases of unilateral cancellation and product non-conformity that occur in MSME practices, show that some business actors have not fully implemented Islamic business ethics consistently. On the other hand, there are also MSMEs who show a high commitment to the principles of shidq and tablīgh, such as conveying product information honestly and openly and providing return services as a form of responsibility. This not only maintains consumer trust, but also has a positive impact on loyalty and business termination in the long term.